MSC in Tendon and Joint Disease: The Context-Sensitive Link Between Targets and Therapeutic Mechanisms - Roth, Susanne Pauline; Burk, Janina; Brehm, Walter; Troillet, Antonia (Frontiers in Bioengineering and Biotechnology, 2022)
Mesenchymal stromal cells (MSC) represent a promising treatment option for tendon disorders and joint diseases, primarily osteoarthritis. Since MSC are highly context-sensitive to their microenvironment, their therapeutic efficacy is influenced by their tissue-specific pathologically altered targets. These include not only cellular components, such as resident cells and invading immunocompetent cells, but also components of the tissue-characteristic extracellular matrix. Although numerous in vitro models have already shown potential MSC-related mechanisms of action in tendon and joint diseases, only a limited number reflect the disease-specific microenvironment and allow conclusions about well-directed MSC-based therapies for injured tendon and joint-associated tissues. In both injured tissue types, inflammatory processes play a pivotal pathophysiological role. In this context, MSC-mediated macrophage modulation seems to be an important mode of action across these tissues. Additional target cells of MSC applied in tendon and joint disorders include tenocytes, synoviocytes as well as other invading and resident immune cells. It remains of critical importance whether the context-sensitive interplay between MSC and tissue- and disease-specific targets results in an overall promotion or inhibition of the desired therapeutic effects. This review presents the authors’ viewpoint on disease-related targets of MSC therapeutically applied in tendon and joint diseases, focusing on the equine patient as valid animal model.